2010
DOI: 10.3844/crpsp.2010.67.70
|View full text |Cite
|
Sign up to set email alerts
|

Ageism in British Columbia: A Brief Report

Abstract: This short report, using Palmore (2001) Ageism Survey, presents data demonstrating the prevalence of Ageism in British Columbia, Canada. Correlation patterns relating to humour, employment, victimization and personal rejection are discussed. Particular emphasis is placed on connecting ageism and relational self-esteem. Sources of respondents include: The Senior Connector, a newspaper distributed throughout British Columbia; the Council of Senior Citizen Organizations (COSCO), several Senior's Recreation centre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…The current study's AVE, CR, Cronbach's alpha, and MaxR revealed that the ageism survey's short 11-item, three-factor Persian version has adequate convergent validity and construct reliability. The findings of this study are similar to previous studies by Palmore ( 23 ), Anderson and Yon ( 54 ), and Erol et al ( 24 ). Therefore, the assessment of ageism among the Iranian population can be anchored on the three valid and reliable subscales.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The current study's AVE, CR, Cronbach's alpha, and MaxR revealed that the ageism survey's short 11-item, three-factor Persian version has adequate convergent validity and construct reliability. The findings of this study are similar to previous studies by Palmore ( 23 ), Anderson and Yon ( 54 ), and Erol et al ( 24 ). Therefore, the assessment of ageism among the Iranian population can be anchored on the three valid and reliable subscales.…”
Section: Discussionsupporting
confidence: 93%
“…However, the findings of the factor structure examination of the original ageism survey were never presented. Anderson and Yon ( 54 ) also found that the items in the ageism survey were grouped into one main factor concurring with the findings of Palmore. Alternatively, Erol et al ( 24 ) evaluated the validity and reliability of the Turkish version of the ageism survey.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…That is, data on insect succession collected from a research study in Florida may not be applicable to a death investigation case in the Nevada desert as the climates vary widely. Some studies have shown at the family level of taxonomic classification succession is stable across many habitats (Anderson, ; Anderson & VanLaerhoven, ; Archer & Elgar, ; Bornemissa, ; Carvalho, Thyseen, Linhares, & Palhares, ; Early & Goff, 1986; Payne, ; Reed, ; Tabor, Fell, & Brewster, ; Wells & LaMotte, ). However, at the more specific level of species, the succession patterns vary with respect to geographic region (Anderson & VanLaerhoven, ; Archer & Elgar, ; Carvalho et al, ; Early & Goff, 1986; Payne, ; Sukontason, Sukontason, Piangjai, & Tippanun, ; Tabor et al, ).…”
Section: The Role Of Entomology In Time Of Death Determinationmentioning
confidence: 99%